Preparation Of Chitosan Derivatives By Polyethyleneimine Modification For The Removal Of Acid Red 88 Dye - Yusof, Nuur Hidayah (2019)
This research is aimed to propose an alternative method to synthesize an inexpensive, green and effective adsorbent for the removal of Acid Red 88 (AR88) from aqueous solution. Chitosan (Cs) was successfully modified with polyethyleneimine (PEI) through a cross-linker either calcium chloride (CaCl2), epichlorohydrin (ECH) or glutaraldehyde (GLA) and identified as CsPC, CsPE and CsPG, respectively. Grafting and cross-linking reactions were established by a one-step synthesis in a closed system by using a Teflon-lined stainless-steel autoclave. During the preparation process, polymer and cross-linker concentrations (1 ‒ 5 % v/v), heating temperature (30 ‒ 80 °C) as well as the heating time (1 ‒ 15 h) were optimized to ensure high adsorption efficiency of the synthesized adsorbents. The optimized adsorbents were analyzed by using the scanning electron microscope coupled with energy dispersive X-ray spectrometer (SEM-EDX), attenuated total reflectance Fourier transform infrared (ATR-FTIR) spectroscopy, X-ray diffraction (XRD), Brunauer- Emmett-Teller (BET) and pH point of zero charge (pHpzc). From these analyses, the adsorbents showed unique morphological, structural and chemical properties that improved their adsorption capabilities towards AR88 dye. The results from the batch adsorption study was analyzed by several isotherm models, namely Langmuir, Freundlich and Temkin.